Effects of dishwashing detergents residues on redox status and cell proliferation in mice liver and kidney - Chahine, Chantal R.; El-Teres, Fadi F.; Chahine, Nathalie R.; Chalhoub, Wissam W. (International Journal of Research in Medical Sciences, 2022)
Background: Commonly known for their cleaning and disinfecting properties, dishwashing detergents containing anionic surfactants can be potentially toxic due to misuse. This study aims to investigate the possible harmful effects of detergents residues persisting on utensils after dishwashing. Methods: Residues were collected after cleaning the utensils in 100 mL of water from 100 households in Beirut, Lebanon. After anionic surfactant determination, water with detergent residues (WDR) was added to drinking water of white mice versus tap water as control: G1 (TW for 2 months), G2 (WDR for 2 months), G3 (TW for 3 months) and G4 (WDR for 3 months), N=6 for each group. Animals were then sacrificed. Biopsies from liver and kidneys were taken for histological examination or preserved at -80°C for biochemical analysis of lipid peroxidation, superoxide dismutase activity, and expression of PI3K/AKT/mTOR pathway proteins by western blotting. Results: Our results showed no significant difference in body weight or histological alteration in groups given WDR versus TW groups. An increase of LP (30%) and a decrease of SOD activity (25%) were noted in the liver tissue of G2 and G4 versus G1 and G3 respectively (p<0.05). In addition, p-AKT and p-mTOR proteins expression regulating cell proliferation were significantly increased in the liver of G4 versus G3 (p<0.05). Conclusions: We concluded that traces of detergents on utensils do not cause an acute pathology, but they could cause oxidative stress to the liver and an over-expression of cancer pathway over a relative long period of time.